2011
DOI: 10.1016/j.scitotenv.2011.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity and uptake of nitroglycerin in a natural sandy loam soil

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. Nitroglycerin (NG) is widely used for the production of explosives and solid propellants, and is a soil contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…It is also used as a therapeutic agent (Rocheleau et al 2011). Double-base propellants used with newer small-arms ammunition typically contain up to 84% NC, with 10% NG (a stabilizer) and up to 6% filler compounds.…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also used as a therapeutic agent (Rocheleau et al 2011). Double-base propellants used with newer small-arms ammunition typically contain up to 84% NC, with 10% NG (a stabilizer) and up to 6% filler compounds.…”
Section: 22mentioning
confidence: 99%
“…The combination of NG, NC, and NQ forms a triple-base propellant mixture. Nitroglycerin can be released into the environment at firing positions, and in the target areas from low-order detonation of propellant (Rocheleau et al 2011). Nitroglycerin is poorly soluble in water and may enter and persist in freshwater environments (USACHPPM 2007).…”
Section: 22mentioning
confidence: 99%
“…Nitroglycerin or glycerol trinitrate (propane-1,2,3-triyl trinitrate) is used in manufacture of dynamite, gunpowder, and rocket propellants, and as a therapeutic agent (Rocheleau et al 2011). Double-base propellants used within newer small-arms ammunition typically contain up to 84% nitrocellulose, with 10% nitroglycerin, a stabilizer, and up to 6% filler compounds.…”
Section: Other Energetic Compounds Nitroguanidinementioning
confidence: 99%
“…The combination of nitroglycerin, nitrocellulose and nitroguanidine forms a triple-base propellant mixture. Nitroglycerin can be released into the environment at firing positions, and in the target areas due to low-order detonation of propellant (Rocheleau et al 2011). Nitroglycerin is water soluble, and may enter and persist in freshwater environments (USACHPPM 2001).…”
Section: Other Energetic Compounds Nitroguanidinementioning
confidence: 99%
“…Published studies on the phytotoxicity of explosives to higher terrestrial plants are scant (Gong et al, 1999;Sunahara et al, 2001;Hannink et al, 2002;Robidoux et al, 2003;Rocheleau et al, 2005Rocheleau et al, , 2006Rocheleau et al, , 2008Rocheleau et al, , 2010Rocheleau et al, , 2011. Winfield et al (2004) found that exposure to RDX (up to 4000 mg/kg soil) during early life stages resulted in adverse responses in sensitive terrestrial plants such as sunflower and sainfoin.…”
mentioning
confidence: 99%